2021
DOI: 10.3390/resources10080079
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Indicator Choice and Normalization in Raw Material Supply Risk Assessments

Abstract: Supply risk assessments are an integral part of raw material criticality assessments frequently used at the country or company level to identify raw materials of concern. However, the indicators used in supply risk assessments to estimate the likelihood of supply disruptions vary substantially. Here, we summarize and evaluate the use of supply risk indicators and their normalization to supply risk scores in 88 methods published until 2020. In total, we find 618 individual applications of supply risk criteria w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 79 publications
0
14
0
Order By: Relevance
“…According to this, the highest water scarcity effects were documented for Issyk-Kul Basin with a 'water consumption/water scarcity impact ratio' of 1:5, followed by Ashburton (~1:5), Huang He (1:4.7) and Colorado River Basin (1:4.4) which were characterized by high water stress intensities. Nickel, molybdenum, gold, copper, zinc 1 Low water stress but classified as 'arid and low water use' according to Gassert et al [69]. (Identification numbers of the GRDC catchment areas as well as basin-specific mining data, water consumption and water scarcity calculations are provided in the Supplementary Materials spreadsheet, see Table S3).…”
Section: Mining's Influence On Regional Water Stress and Carrying Capacitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this, the highest water scarcity effects were documented for Issyk-Kul Basin with a 'water consumption/water scarcity impact ratio' of 1:5, followed by Ashburton (~1:5), Huang He (1:4.7) and Colorado River Basin (1:4.4) which were characterized by high water stress intensities. Nickel, molybdenum, gold, copper, zinc 1 Low water stress but classified as 'arid and low water use' according to Gassert et al [69]. (Identification numbers of the GRDC catchment areas as well as basin-specific mining data, water consumption and water scarcity calculations are provided in the Supplementary Materials spreadsheet, see Table S3).…”
Section: Mining's Influence On Regional Water Stress and Carrying Capacitiesmentioning
confidence: 99%
“…In particular, high-technology applications require a large variety of minerals and metals, which in some cases are referred to as critical raw materials due to increasing concerns about their limited availability and potential supply shortages. Hence, primarily during the last two decades, criticality assessment methods have been developed and constantly evolved to screen mineral commodity markets in order to identify raw materials of concern [1,2]. However, the global expansion of resource extraction, particularly mining and refining of metals, is also characterized by environmental concerns as the mining and refining of technology-relevant metals have significant impacts on ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…In short, in many categories, we believe that our approach can complement existing approaches in many cases. Resource nationalism strategies of supplying countries 10 Embargo/trade barriers Helbig et al [6] organized the indices used in existing supply risk assessment research. They proposed the following 10 categories: concentration, scarcity, political instability, regulations, by-product dependence, dependence on primary production, demand growth, lack of substitution options, price volatility, import dependence, and others.…”
Section: Pros and Cons Of Using Internet News Articlesmentioning
confidence: 99%
“…Helbig et al [6] reviewed existing studies from both the indicator selection and normalization perspectives. They revealed that the 88 studies reviewed employed 618 indicators, all of which can be classified into 10 categories.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure access to, and use of, resources in the future in a justifiable manner, these issues have to be addressed. This can be done using criticality assessments that aim at hotspot analysis and risk mitigation [11]. In recent years, several assessment methods regarding resource efficiency and criticality have been developed [12,13].…”
Section: Introductionmentioning
confidence: 99%